FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN KERJA PERAWAT RAWAT INAP RUMAH SAKIT UMUM DAERAH TUGUREJO SEMARANG - Nurfrida Pratomo Putri; Ayun Sriatmi; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Job satisfaction is a reflection of the workers’ feeling in their work. It can be shown from employee's attitude to the work and their working environment. The nurse's job satisfaction needs to get serious attention from hospital management because nurse holds the most important service role in the hospital. The objective of the research was to determine the related factors with nurse job satisfaction in inpatient Tugurejo Hospital Semarang. The research used quantitative method with cross sectional approach. The sample used in the research was 80 inpatient nurses of Tugurejo Hospital Semarang with proportional random sampling method. The research used univariate analysis, bivariate analysis by Rank Spearman test. The result showed that the respondents had good recognition (67,5%), responsibility (55%), potential development (60%), promotion opportunities (51,3%), income (66,3%), working conditions (60%), hospital administration and policy (82,5%), interaction between individuals (90%), supervision (66,3%). Variables related to inpatient nurses’ job satisfication of Tugurejo Hospital Semarang were recognition (p = 0,000), potential development (p = 0,000), promotion opportunities (p = 0,000), income (p = 0,000), working conditions = 0.000), hospital administration and policy, interaction between individuals (p = 0,000) and supervision (p = 0,000). Meanwhile, unrelated variable to inpatient nurses’ job satisfication of Tugurejo Hospital Semarang was responsibility (p = 0,365). In order to manage nurse job satisfaction, the hospital management should be able to create a pleasant working environment, provide positive feedback, and able to improve the career path system.